Strategi penerapan fintech sebagai upaya bank syariah dalam peningkatan inklusi keuangan - Azkya, Vaizul (Maliki Interdisciplinary Journal, 2025)
This study discusses the strategy of implementing financial technology (fintech) as an effort by Islamic banks to enhance financial inclusion in Indonesia. Financial inclusion is a crucial priority in strengthening the national economy, and fintech plays a significant role in providing easier and more affordable access to financial services. This research employs a qualitative approach with a descriptive-analytical method, identifying various opportunities and challenges faced by Islamic banks in adopting fintech. The findings indicate that fintech not only improves operational efficiency and accessibility but also encourages the innovation of products and services that align with Sharia principles. However, challenges such as data security and digital literacy need to be addressed to fully leverage the potential of fintech. This study offers practical recommendations for Islamic banks to optimize the implementation of fintech in achieving better financial inclusion goals.